AN ANALYSIS OF ADDRESS TERMS BASED ON KINSHIP SYSTEM OF BATAK TOBA USED BY BATAKNESSE IN PADANG - Sarnyanti Lumbanbatu; Jufrizal Jufrizal; Delvi Wahyuni (Universitas Negeri Padang, 2018)
The word address term is the word person use to call or greet others. Batak Toba language has various forms of greeting words used in communicating with someone. This study aims to find out the forms of the word greetings based on kinship or family system used by Batak Toba people who live in Padang Pasir Parupuk Tabing as nomads. This study will also explain and describe the communicative function the use of greeting. The method used in this research is descriptive method that describes and process data based on facts that exist in the field. This research is focused on the forms and functions of the address terms word in Batak Toba language. Data were collected through interview with some informants and made notes. In this study, the informants are Batak Toba People who has blood relations and marriage. Data were analyzed based on the forms of address terms based on kinship system of Batak Toba. The results of research indicate that there are various address terms used by Batak Toba ethnic especially in kinship relationship based on lineage and marriage that used by Batak Toba people. Interestingly, there are several forms of greeting words that are similar to each other.